Cultura da Wikipédia como Política de capacitação compartilhada em meio digital de socialização do conhecimento - Jorente, Maria José Vicentini [UNESP] (My University, 2011)
Presents a developing laboratory within History of Culture, subject taught in the Library and Archive Studies at UNESP (Marilia). The project is based upon the foundations of research line Information and Technology: students from the second under graduation year participate in the improving of 27 entries in Portuguese language Wikipedia. The aim is to capacitate for scientific reading and writing in digital media, habilitate for the information identification and recuperation and for the interpretation and understanding of formal and contents aspects and its reorganization. It includes activities of search, selection, remix and republishing of texts, images, audio and videos in the convergence of diverse hypertext information sources, supported by tutors with strategic abilities in digital environments. In this sense it was adhered to the international Wikipedia Foundation University Campus Ambassadors project. It’s also aimed to induce sharing and collaboration behaviors with the purpose of creating necessary habits for the informational empowerment in Brazil. As methodology is to optimize the work of individuals already trained in wiki culture and to create in within the subject information sharing programs with a more specialized bias, giving greater credibility to the digital environment. The environment syntaxes helps in the learning of the complementary skills of reading and writing and offers itself as an open repository from which information can be reused. It is, thus, an empowerment strategy in the search of autonomy and self reliance considering intersemiotic knowledge in the edition, visualization and understanding of information in the social web. A second step of a verifying research on the environment’s credibility after the consolidation and dissemination of the entries improvement work is proposed.

Apresenta-se laboratório em desenvolvimento no âmbito da disciplina História da Cultura, ministrada nos cursos de Arquivologia e Biblioteconomia da Unesp (Marília), que se vincula à linha de pesquisa Informação e Tecnologia: alunos do segundo ano da graduação participam na melhoria de 27 verbetes em língua portuguesa na Wikipédia. Busca-se capacitar para a leitura e a escrita científica no ambiente digital, habilitar para a identificação e recuperação de informações e para interpretação e compreensão de aspectos formais e conteudísticos da informação e sua reorganização. Compreende assim atividades de busca, seleção, remix e republicação de textos, imagens, áudio e vídeos na convergência das diversas fontes de informação hipertextuais, apoiadas por tutores com domínio estratégico dos ambientes digitais. Aderiu-se para isso ao projeto internacional da Fundação Wikimedia de Embaixadores de Campi universitários. Visa também induzir comportamentos de compartilhamento e colaboração em rede com finalidade de criar hábitos necessários para empoderamento informacional no Brasil. Como metodologia, se otimiza o trabalho de indivíduos já formados na cultura wiki, e cria-se na disciplina programas de compartilhamento de informações com viés mais especializado, dando ao ambiente digital maior credibilidade. O ambiente tem sua própria sintaxe que ajuda no aprendizado das habilidades complementares à leitura e à escrita e se oferece como repositório aberto em que a informação poderá ser reutilizada. Trata-se, assim, de estratégia de autonomia e suficiência que considera conhecimentos intersemióticos na edição, visualização e compreensão de informação na web social. Propõe-se segunda etapa de verificação da confiabilidade do ambiente após o trabalho de consolidação e divulgação da melhoria dos verbetes.
Wikipedia culture as shared capacitating politics in digital media of knowledge socialization
Keywords: Informação e Tecnologia; Cultura Digital; Compartilhamento; Wikipedia; Web Colaborativa